Analysis of CDM experience in Morocco and lessons learnt for West African Economic and Monetary Union. Case study: Benin, Burkina Faso, Niger and Togo - Honorat Satoguina (Hamburg Institute of International Economics (HWWA), 2006)
This study assesses the CDM potential in Benin, Burkina Faso, Niger and Togo. Morocco has been used as an example, as it is quite advanced in developing an impressive CDM project portfolio. The study focuses not only on the absolute greenhouse gas abatement potential of these countries, but also assesses the comparative CDM endowment on the basis of an holistic analysis of each country, thereby highlighting the relative position of Benin, Burkina Faso, Niger and Togo in the global CDM market. The competitiveness of these four members of the West African Economic and Monetary union is assessed taking into consideration three pillars, namely ,,Potential supply size – countries` facts“, ,,Country business climate“ and ,,Country CDM institutions and CDM project experience“. Overall competitiveness is analysed, as well as which activities could best maximize opportunities to convert theoretical mitigation options into real CDM investments. The case study countries have a similar CDM climate, characterised by a low CDM potential, low FDI inflows and low financial support from the international CDM community. These factors help explain the low CDM activities in these countries. Currently, only small-scale CDM projects could be developed in these countries in energy efficiency and renewable energy sectors. As transaction costs and risks are high for these project types, it is likely that in the short- and mid-term, only special CDM project support programmes in LDC such as Community Development Climate Fund (CDCF), Bio Carbon Fund (BioCF) and Africa Assist may provide a chance for participation in the international CDM market.
Keywords: O55; L71; O16; Q40; L70; Q20; O14; O12; O11; 330; CDM potential; CDM viability factors; Energy intensity; energy consumption; CO2 Emissions intensity; Country investment climate